STRATEGI PEMERINTAH DALAM PENGEMBANGAN EKOWISATA (STUDI DI KAWASAN TAMAN NASIONAL BUKIT TIGA PULUH KABUPATEN INDRAGIRI HULU PROVINSI RIAU) - Marta, Auradian (Universitas Riau, 2014)
This study departs from the problems in the development of the Taman Nasional BukitTigapuluh (TNBT) in the region Indragiri Hulu Riau Province namely the destruction ofecosystems and inadequate infrastructure. This study seeks to examine the government's strategyin the development of the Taman Nasional Bukit Tigapuluh (TNBT). The research method inthis study using kualititatif approach. This study showed that in the development of theTamanNasional Bukit Tigapuluh (TNBT) includes planning, utilization and control is not runningoptimally. Synergy and cooperation between government agencies such as the Taman NasionalBukit Tigapuluh (TNBT), the Regional Government of Riau Province, Local GovernmentIndragiri upstream has not gone well so that the development of eco-tourism area is likely to beslow.Keywords: ecotourism, government strategy, the development